Is V.O2peak a valid estimation of V.O2max in swimmers with physical impairments? - Feitosa, W. G.; Barbosa, T. M.; de A. Correia, R.; de S. Castro, F. A. (Research Quarterly for Exercise and Sport, 2020)
Purpose: Peak and maximal oxygen uptake (V.O2peak and V.O2max, respectively) are used in assessing aerobic power. For swimmers with physical impairments, it is unclear whether the physiological variables obtained in 200-m and Nx200-m tests are similar. The objective of this study is to assess the validity of V.O2peak as an estimator of V.O2max and complementary physiological variables, in particular, carbon dioxide production (V.CO2), respiratory exchange ratio (RER), minute-ventilation (V?E) and absolute (HR) and relative (%HRmax) heart rates—which were obtained in a time trial test (200-m) and an incremental intermittent test (Nx200-m) performed by swimmers with physical impairments. Methods: Eleven well-trained swimmers with physical impairments performed 200-m all-out and Nx200-m from low to all-out (controlled by a visual pacer), both with a respiratory valve system and a portable gas analyzer. Results: A paired Student`s t-test showed no statistical difference (p > .05) for all comparisons. The intraclass correlation coefficient (ICC) was 0.97 and 0.98 for V?O2 in l/min and ml/kg/min, respectively; ICC = 0.75 to 0.9 for V.CO2 (l/min and ml/kg/min), V.E (in l/min) and HR (beats/min); ICC = 0.5 and 0.75 for %HRmax; and ICC < 0.5 for RER. Passing-Bablok regression showed that the dispersions were acceptable, considering the proportionality, except for HR and %HRmax. Bland-Altman method showed a high level of agreement for all variables. Conclusions: The V.O2peak and V.O2max, as well as the physiological variables V.CO2 and HR obtained, respectively, by 200-m and Nx200-m tests in swimmers with physical impairment were not different.